A tanulmányi jogviszonyból eredő közigazgatási perek (Administrative Lawsuit Arising from a Study Relationship) - Zsuzsanna Árva (KözigazgatásTudomány)
A specific type of administrative lawsuit is lawsuit arising from a study relationship. Their main characteristic is the nature of the rules applied. The courts are required to apply not only the rules of law but also the institutional rules, which, given the framework nature of the public rules, often make up the bulk of the applicable rules. The origins of university jurisdiction – as part of autonomy – go back much further than administrative litigation. This institution, which used to include blood court, has evolved considerably over the centuries and has now been increasingly dominated by elements of consumerism. This process began in the Anglo-Saxon countries as early as the 1960s, while in Hungary it only became possible to bring a lawsuit in 2003, so the latest trends in lawsuits arising from the study relationship can be deduced from the types of lawsuits typical of those countries. Accordingly, the study traces the path of university lawsuit in Hungary, some experiences abroad and typifies Hungarian lawsuit.